Understanding the Cation Exchange Affinity in Modified-mmt Catalysts for the Conversion of Glucose to Lactic Acid - Shikh Mohd Shahrul Nizan Shikh Zahari; Farah Wahida Harun; Nur Fatin Izzati Che Sam; Kholoud M. H. Elzaneen; Mahfuzah Samirah Ideris; Hazeeq Hazwan Azman (Royal Society of Chemistry, 2024)
Indexed by WOS/Scopus/ERA